Translation Strategies of Idiomatic Expressions in the Novel The Song of Achilles - Amara Josephine Mendi; Putu Ayu Asty Senja Pratiwi; Ni Luh Sutjiati Beratha (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The purpose of this study is to identify a few types of idiomatic expressions and the translation strategies used to translate the Idiomatic Expressions in the novel The Song of Achilles. The data was collected from the English version of the novel and its Indonesian translation Nyanyian Achilles. The method applied in this study is a descriptive qualitative method. To classify the Idiomatic Expressions, the researcher used the theory of types of idioms proposed by Fernando (1996), while the analysis process used the translation strategies of idioms proposed by Baker (2018). The results show that 38 idioms are found in the novel and all three types of idiomatic expressions were found. Pure idioms appeared most frequently with 17 data, followed by semi-idioms with 11 data and literal idioms with 10 data. Furthermore, five out of six strategies were identified with the most frequently used strategy being translation by paraphrase with 18 data. The least used strategy was translation by omission of the entire idiom with 1 data. Meanwhile, the strategy of borrowing was not found in the novel.